Pushing the limits - McGarry, Katie (Harlequin Teen, 2012)
Rendered a subject of gossip after a traumatic night that left her with terrible scars on her arms, Echo is dumped by her boyfriend and bonds with bad-boy Noah, whose tough attitude hides an understanding nature and difficult secrets.